Marjambar as a Symbolic Interaction of the Bunga Bondar Society in Sipirok District - North Sumatra - Indra Muda; Syafruddin Ritonga; Beby Masitho Batubara; Nina Angelia; Waridah Pulungan (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Bunga Bondar Village has a unique culture called Marjambar. Marjambar is held   by distributing pastries typical of the local community during religious holidays, which are ahead of Eid al-Fitr for Muslims and one day before New Year for Christians. This study aims to analyze the multiculturalism model that exists in marjambar. This study  uses Mead's symbolic interaction theory. The research method of this study is  a qualitative descriptive approach, while data collection technique is conducted through  observation, interviews and documentation.  A total of eight research informants were interviewed, comprising two Islamic religious leaders, two Christian religious leaders, one traditional leader, one youth leader, two village apparatuses. This research found that in realizing the values of multiculturalism there is a philosophy of life "thick water is thicker, brotherly relations and we are one blood (alkot aek alkotan dope mudar dan hita dongan samudar). The implementation of marjambar local wisdom reflects the value of cosmopolitan multiculturalism in  which  each individual is  free with his cultural life, without intimidation and domination, thus creating an attitude of concern between people of  different faiths and  ethnic groups. In conclusion, intercultural life which exists side by side shows equality between people. The researcher suggests that local governments through schools provide formal and informal education to educators who stay at the forefront of the effort to disseminate local wisdom among students. It is necessary to provide bailout funds to preserve marjambar local wisdom, for example, for  monthly meetings between religious leaders, community leaders, traditional leaders and the community.